Succinyl-CoA Synthetase: New Antigen Candidate of Bartonella bacilliformis - Gomes, C (2016)
This study aimed to identify new B. bacilliformis antigenic candidates that could lead to a new diagnostic tool able to be implemented in endemic rural areas. RT-PCR and the high levels of positivity for specific ELISAs demonstrate high levels of B. bacilliformis exposure and asymptomatic carriers among inhabitants. The new antigens identified might be used as a new rapid diagnostic tool to diagnose acute Carrion’s disease and identify asymptomatic carriers.